The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2117/psysoc.2012.80
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Emotional Memories: A Review of Evidence From Brain Imaging Studies

Abstract: What are the neural markers of encoding and retrieving emotional events with increased efficacy? In recent years, this question has captured the attention of cognitive neuroscientists who fervently engaged in addressing it using a multitude of approaches. The present review discusses evidence from brain imaging studies investigating the neural correlates of the memory-enhancing effect of emotion in healthy human participants. The available evidence points to two main mechanisms: one direct involving the medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 177 publications
8
75
0
3
Order By: Relevance
“…As shown in past studies (e.g., Dolcos & Denkova, 2008;Mather & Sutherland, 2009), participants remembered both positive and negative images equally better than neutral images. Despite the similar memory enhancement effects, presentation of positive and negative pictures had different impacts on subsequent understanding of the solutions to problems requiring insight.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As shown in past studies (e.g., Dolcos & Denkova, 2008;Mather & Sutherland, 2009), participants remembered both positive and negative images equally better than neutral images. Despite the similar memory enhancement effects, presentation of positive and negative pictures had different impacts on subsequent understanding of the solutions to problems requiring insight.…”
Section: Discussionsupporting
confidence: 71%
“…The results of past studies have revealed that both positive and negative stimuli are remembered better than neutral stimuli if they are matched in arousal levels (e.g., Dolcos & Denkova, 2008;Hamann, Ely, Grafton, & Kilts, 1999;Mather & Sutherland, 2009). These findings suggest that arousal is more crucial than valence in the effects of emotion on memory.…”
Section: Studymentioning
confidence: 99%
“…Emotional arousal increases activity in the amygdala and hippocampus (Denkova, Dolcos, & Dolcos, 2012; Dolcos, LaBar, & Cabeza, 2004a; Dolcos et al, 2004b). This enhanced activity is suggested to modulate memory consolidation (Dolcos et al, 2004b), resulting in better memory performance for emotionally arousing material relative to neutral (Dolcos, Denkova, & Dolcos, 2012; Dolcos et al, 2004b; Kensinger & Corkin, 2004). These findings add to the body of literature that suggests emotional materials are better remembered than non-emotional materials and that this effect is driven by arousal (Dolcos et al, 2004b; Kensinger & Corkin, 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at both valence and arousal dimensions, Adelman and Estes (2013) have shown that the memory benefit for emotionally valenced words, whether positive or negative, over neutral words may be independent of arousal. The necessity to test the conjoint effect of valence and arousal is further supported by neuroimaging studies, which suggest that arousal and valence influence memory through two distinct neural mechanisms (Dolcos et al, 2004; Kensinger and Corkin, 2004; for a review see Murty et al, 2010; Dolcos et al, 2012). …”
Section: Introductionmentioning
confidence: 99%